Determinant of the Alkaloidal Levels in Cryptolepis Sanguinolenta (Lindl.) Schtr - Ameyaw, Y.; Akotoye, H.K.; Pappoe, A.N.M.; Dampared, S.B.; Opoku Boahen, Y.; Owusu-Ansah, E.; Adomako (Asian Journal of Chemistry, 2010)
This study is focused on the importance of the enrichment index of the soils on the alkaloidal levels of the plant organs of Cryptolepis sanguinolenta, a medicinal plant in two districts in the Eastern Region of Ghana. The extraction method was used to quantify the alkaloid in the organs while the irradiation method was also used to quantify the soil elements needed for the computation of the enrichment index of the soils. Results gathered show the enrichment of the soils to be less than 1. Therefore the soils of the locations are considered to be non-toxic. Pepease had an enrichment index of 0.22; Mamfe, 0.13 and Abonse, 0.14. The nature of the enrichment index of the soils fluctuated concurrently as the alkaloidal contents of the plant organs.